P300 The Clinical Effectiveness Of Domiciliary Non-invasive Ventilation (niv) In Patients With End-stage Copd. (10th November 2014) - Dretzke, J; Dave, C; Blissett, D; Mukherjee, R; Price, M; Bayliss, S; Wu, X; Jordan, R; Jowett, S; Moore, DJ; Turner, AM
Abstract : Background: NIV is very effective when used acutely in hospital during acute exacerbations of COPD, however, evidence supporting its use in a home setting for more stable COPD patients is limited. In the UK domiciliary NIV is considered by many clinicians on health economic grounds in patients after three hospital admissions for acute hypercapnic respiratory failure. Previous systematic reviews of domiciliary NIV have been limited in scope and required updating. Methods: Standard systematic review methods were used for identifying relevant clinical and cost-effectiveness studies of any appropriate design assessing NIV compared to usual care, or comparing different types of NIV. Risk of bias was assessed and checked. Primary effectiveness outcomes (mortality, hospitalisations, exacerbations and quality-of-life) were combined using random effects meta-analysis. Results were grouped into patients given NIV within 6 weeks of a hospital admission requiring inpatient NIV and those given NIV when stable. Results: Thirty controlled effectiveness studies were identified reporting a variety of outcomes, together with 65 uncontrolled studies. Benefit from NIV in terms of survival and hospital admissions in controlled studies was variable, and where present appeared most marked in post-hospital patients (based on limited evidence). For more stable patients, a modest volume of evidence found no benefit from NIV for survival and some non-significant beneficial trends for hospitalisations and quality-of life. No conclusions could be drawn regarding potential benefit from different types of NIV due to limited study sizes and heterogeneity. Conclusions: Domiciliary NIV has greatest effect when used after a hypercapnic exacerbation and might improve hospitalisation rates and mortality in this group of patients. There is no benefit if used in stable, normocapnic patients. This abstract summarises independent research funded by the National Institute for Health Research (NIHR) under its HTA Programme (Ref 11/27/01). The views expressed are those of the author (s) and not necessarily those of the NHS, the NIHR or the Department of Health.